Design and modeling of a flexible longitudinal zigzag structure for enhanced vibration energy harvesting. (February 2017) - Zhou, Shengxi; Chen, Weijia; Malakooti, Mohammad H; Cao, Junyi; Inman, Daniel J
The use of piezoelectric materials for vibration energy harvesting at low frequencies is challenging and requires innovative structural design. Here, a flexible longitudinal zigzag structure is developed to enhance energy harvesting at low-frequency ambient vibrations. The proposed structure is composed of orthogonal beams which enable vibration energy harvesting in two directions. A theoretical model based on Euler–Bernoulli beam theory is formulated to study the dynamic response of the structure under free vibrations. The free vibration analysis demonstrates that low operating frequencies can be obtained by increasing the number of, and/or the length of, beams in the proposed structure. To validate the accuracy of the developed theoretical model, finite element analysis is performed using ANSYS. On verification of the model's accuracy, the piezoelectric effect of the active beams is considered in the model to evaluate the energy harvesting performance of the proposed flexible longitudinal zigzag structure. Numerical results demonstrate that the output voltage and the working frequency of these energy harvesting structures can be tailored through simply altering the number of beams. Overall, the results indicate that the proposed structure is capable of efficient energy conversion at low frequencies, which makes them suitable for a wide range of working conditions.